SIGNIFICANCE OF INTERACTIONS BETWEEN GENETIC AND ENVIRONMENTAL FACTORS IN ETIOLOGY OF MULTIPLE SCLEROSIS - Jovanović, Aleksa; Novakovic, Ivana; Mesaroš, Šarlota; Pekmezovic, Tatjana (Medicinski podmladak, 2024)
Multiple sclerosis (MS) is an immune-mediated disorder of central nervous system. It most frequently occurs in young female adults, and the prevalence increases with latitude. So far, over 200 genes, loci and single nucleotide polymorphisms (SNPs) have been linked with MS, although each one contributing only slightly in the overall etiology of the disease. The HLA-DRB1*15:01 haplotype has been shown to have the strongest association with MS occurrence risk in genome-wide association studies (GWAS), while HLA-A*02 has been shown to have a protective effect. The exact etiology of MS is still unclear, but there seems to exist interplay between genetic burden of an individual, and environmental factors which contribute to MS occurrence such as Epstein-Barr virus (EBV) infection, vitamin D levels, smoking status, and early life obesity. An interaction between HLA-DRB1*15:01 and EBV infection, the strongest environmental risk factor for MS, has been observed. It has been suggested that this interaction is a result of HLA-DRB1*15:01 acting as a coreceptor for EBV, thus providing a pathophysiological explanation connecting environmental with genetic MS risk factors. A recent study including participants from two case-control studies with over 13.000 individuals showed that an interaction exists between sun exposure, vitamin D levels, and HLA-DRB*15:01 carrier status, leading to increased risk of MS in individuals with lower sun exposure, vitamin D deficient, and HLA-DRB*15:01 positive. The interaction of HLA-DRB1*15:01 with smoking has been observed in a meta-analysis, while the same study only showed an interaction of smoking with the absence of HLA-A*02 in a subset of studies. The risk of MS has been show to vary in obese individuals, with obese individuals with the susceptible genotype (HLA-DRB1*15:01+, HLA-A*02-) having 16x higher odds of having MS compared with non-obese persons with a non-susceptible genotype.
Keywords: multiple sclerosis, interaction, genetics, risk factors, review